PENGELOLAAN SAMPAH TERPADU 3R (REDUCE-REUSE-RECYCLE), PEMBUATAN KOMPOS DARI SAMPAH ORGANIK - Dharma, Budhi (Universitas Diponegoro, 2011)
Abstract Â Garbage represents the waste product of household activities in solid as well as half solid forms. They derive from human settlement, market, commercial areas, offices, industrial zones, ranch and other public facilities. Implementing the 3-R progrom (Reduce-Reuse- Recycle), such as : separating various kinds of garbage from its source, development of garbage composting and integrated use of garage recycling product in human settlement area is regarded as an effective way to solve the garbage problem.The 3 - R program is expected to increase understanding and awareness among the community members about environmental health and also to minimize garbage disposal to the final garbage disposal plant. Â Key word: garbage, reduce, reuse, recycle, compos